Climate Change Perception of Farmers and Its Effect on the Technical Efficiency of Rice Production - Md. Motiur Rahman; Md. Toriqul Islam; Mst. Esrat Jahan (CV. Truly Science Publishing, 2025)
The study analyzed the impact of climate change perception of farmers on the technical efficiency of rice production in North-West Bangladesh. Cobb-Douglas stochastic frontier approach, including maximum likelihood estimation and technical efficiency estimation, was employed to determine the technical efficiency of Boro rice production in Nilphamari, Bangladesh. Required data were collected from 108 Boro rice-producing farmers of Domar upazila under Nilphamari district, selected using a convenient sampling technique. In analyzing the data, farmer-specific technical efficiency scores were estimated using the Cobb-Douglas stochastic frontier approach, including maximum likelihood estimation and technical efficiency estimation. The weighted average index was used to measure climate change perception of the farmers, and the mean weighted climate change perception index is 19.25. The study's findings also revealed that the technical efficiency of Boro rice production in Domar Upazila under Nilphamari district is 87%. It is also found that education, access to non-farm income, access to credit, access to organic fertilizer and ownership of land, access to climate awareness training, and access to the government. subsidy and all the factors of production are the significant factors that affect the level of technical efficiency. The current technical efficiency indicates that Boro rice production in the study area has been operating below the maximum level of production frontier, and given the available technology, farmers can increase their production by 13% through improving their awareness related to attributes and by making optimal use of factors of production or inputs.